1994
DOI: 10.1159/000244118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral IGF-I or IGF-II on Digestive Organ Growth in Newborn Piglets

Abstract: To study whether colostrum-borne growth factors are responsible for the rapid GI tissue growth in naturally suckled newborn animals, newborn unsuckled piglets were bottle-fed for 24 h with infant milk formula with or without addition of 2 μg/ml of recombinant human insulin-like growth factor-I (IGF-I) or insulin-like growth factor-II (IGF-II), a level which approximated that of porcine colostrum. The animals were then sacrificed for measurements of their digestive organ weights and contents of protein, RNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
3
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 27 publications
3
50
3
6
Order By: Relevance
“…Piglets receiving the IGF-I-supplemented formula consumed approximately 200 mg·kg-BW −1 ·d −1 (Houle et al, 1995). Consistent with previous studies, two studies Xu et al, 1994) indicated that weight gain and final BW were unaffected by oral IGF-I administration. Serum IGF-I (Burrin et al, 1995b;Houle et al, 1995), serum IGF-II (Houle et al, 1995), or serum IGFBP profiles (Houle et al, 1995) were also unaffected by oral IGF-I intake, supporting our previous study that suggested that absorbed [ 125 I]IGF-I made a negligible contribution to serum IGF-I (Donovan et al, 1996).…”
Section: Insulin-like Growth Factors I and Ii Four Studiessupporting
confidence: 87%
See 3 more Smart Citations
“…Piglets receiving the IGF-I-supplemented formula consumed approximately 200 mg·kg-BW −1 ·d −1 (Houle et al, 1995). Consistent with previous studies, two studies Xu et al, 1994) indicated that weight gain and final BW were unaffected by oral IGF-I administration. Serum IGF-I (Burrin et al, 1995b;Houle et al, 1995), serum IGF-II (Houle et al, 1995), or serum IGFBP profiles (Houle et al, 1995) were also unaffected by oral IGF-I intake, supporting our previous study that suggested that absorbed [ 125 I]IGF-I made a negligible contribution to serum IGF-I (Donovan et al, 1996).…”
Section: Insulin-like Growth Factors I and Ii Four Studiessupporting
confidence: 87%
“…The lack of effect on overall body weight or tissue weights observed after consumption of colostral levels of IGF-I (500 mg/L) for 14 d suggests that orally administered IGF-I at a high physiological dose is not a major regulator of neonatal growth (Houle et al, 1995). Although a pharmacologic dose of IGF-I or IGF-II (2,000 mg/L) increased pancreatic growth in the first 24 h of life (Xu et al, 1994), the physiological relevance of this finding is questionable. With respect to the intestine, results thus far suggest that the magnitude of the response is affected both by the dose administered and the duration of the exposure.…”
Section: Insulin-like Growth Factors I and Ii Four Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Donovan et al (1997) and Hammon and Blum (1997), IGF-I is not absorbed in the small intestine in calves and pigs, even immediately after birth, though colostrum ingestion causes a marked increase of IGF-I in blood plasma (Egli and Blum, 1998). Feeding piglets with an infant formula supplemented with IGF-I and IGF-II leads to a higher DNA content in the stomach tissue and increases cell proliferation in the upper gut as compared with infant formula alone (Xu et al, 1994). In neonatal calves, orally administered recombinant human IGF-I stimulated growth of the intestine as evidenced by [ 3 H]-thymidine incorporation into the enterocyte (Baumrucker et al, 1994), but histological examination of the intestinal mucosa did not reveal any effect (Blum and Hammon, 2000).…”
Section: Insulin-like Growth Factormentioning
confidence: 99%